Energy balance optimization of sugarcane crop residual biomass - Pereira Sartori, Maria Marcia; Florentino, Helenice de Oliveira (Elsevier B.V., 2007)
This work presents a mathematical model for helping mills choose sugarcane varieties for planting. It maximizes crop residual biomass energy balance by considering the difference between generated and consumed energy in the process of transferring this biomass from the field to the processing center; it takes into account enterprise demand restrictions and cane planting area. For this full zero-one linear programming techniques were proposed. The model is viable for choosing sugarcane varieties that would benefit sugarcane production and industrial systems, by reducing crop residue and increasing final energy production. (c) 2006 Published by Elsevier Ltd.
Keywords: model; integer programming; harvesting residue; sugarcane